Dynamical and elastic properties of MgSiO3 perovskite (bridgmanite). Issue 6 (29th March 2016) - Wehinger, Björn; Bosak, Alexeï; Nazzareni, Sabrina; Antonangeli, Daniele; Mirone, Alessandro; Chaplot, Samrath Lal; Mittal, Ranjan; Ohtani, Eiji; Shatskiy, Anton; Saxena, Surendra; Ghose, Subrata; Krisch, Michael
Abstract: We report on the lattice dynamics of MgSiO3 perovskite (bridgmanite). Phonon spectroscopy was performed employing inelastic X‐ray scattering from single crystals, and the results were confronted to ab initio calculations. We observe a remarkable agreement between experiment and theory, and provide accurate results for phonon dispersion relations, the vibrational density of states, and the full elasticity tensor. The present work constitutes an important milestone fully validating the lattice dynamics calculation against precise experimental evidence and marks a starting point to extend this kind of combined studies to the high‐pressure and high‐temperature conditions directly relevant for the physical properties and chemical composition of Earth's lower mantle. Key Points: Lattice dynamics of MgSiO3 ‐bridgmanite Phonon spectroscopy by inelastic X‐ray scattering Lattice dynamics by density functional perturbation theory